2022
DOI: 10.1371/journal.pone.0272936
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescribing and dispensing practices in regional and national referral hospitals of Eritrea: Evaluation with WHO/INRUD core drug use indicators

Abstract: Rational use of medicine (RUM) for all medical conditions is crucial in attaining quality of healthcare and medical care for patients and the community as a whole. However, the actual medicine use pattern is not consistent with that of the World Health Organization (WHO) guideline and is often irrational in many healthcare setting, particularly in developing countries. Thus, the aim of the study was to evaluate rational medicine use based on WHO/International Network of Rational Use of Drugs (INRUD) core drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 25 publications
2
17
4
Order By: Relevance
“…This study discovered that the four-IRDP was 3.38, which is less than the optimal four. In addition, when evaluating the four indicators, this result was lower than the 3.89 and 3.83 revealed, respectively, by the Eritrea regional and national referral hospitals study, North-East Ethiopia (Siele et al, 2022 ; Wendie et al, 2021 ). However, this is higher than the 2.78 reported from Sri Lanka study (Galappatthy et al, 2021a ).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This study discovered that the four-IRDP was 3.38, which is less than the optimal four. In addition, when evaluating the four indicators, this result was lower than the 3.89 and 3.83 revealed, respectively, by the Eritrea regional and national referral hospitals study, North-East Ethiopia (Siele et al, 2022 ; Wendie et al, 2021 ). However, this is higher than the 2.78 reported from Sri Lanka study (Galappatthy et al, 2021a ).…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, to assess drug usage comprehensively, Indices such as Index of Rational Facility Specific Drug Use (IRFSDU) and Index of Rational Drug Prescribing (IRDP) were developed by Zhi and Zhang (Akl et al, 2014 ; Siele et al, 2022 ; Wendie et al, 2021 ). To calculate indices of non-pharmacy and injection use safely, the following formula was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Good drug-prescribing knowledge and practices are the most important indicators of quality healthcare service (12). Scientific evidence-based correct drug indications and a properly filled out prescription are critical parameters of quality pharmacotherapy delivery (2).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines rational use of medication as the provision of “right medicine to the right patient, in the right dose, for the right duration of time, at the most economical cost to the patients and their community” [ 8 ]. According to the WHO, it is estimated that over half of all medicines are not properly prescribed, dispensed, or taken, leading to adverse patient outcomes [ 9 ]. Irrational use of medications has become a global problem.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have assessed general and antibiotic specific prescribing practices employing WHO core indicators in different settings, community pharmacies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ], primary health care centers [ 22 , 23 ], general [ 24 ] and referral [ 9 ] hospitals. The majority of these studies reported deviation from the optimum values of WHO core indicators, highlighting the need for regular review of drug use practices, education and training for health care providers on responsible drug use, and fostering a culture of continuous quality improvement.…”
Section: Introductionmentioning
confidence: 99%